2014
DOI: 10.1080/10934529.2014.865447
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative degradation of sulfathiazole by Fenton and photo-Fenton reactions

Abstract: This article presents experimental results on 47 μmol L(-1) sulfathiazole (STZ) degradation by Fenton and photo-Fenton reactions using multivariate analysis. The optimal experimental conditions for reactions were obtained by Response Surface Methodology (RSM). In the case of the Fenton reactions there were 192 μmol L(-1) ferrous ions (Fe(II)) and 1856 μmol L(-1) hydrogen peroxide (H2O2), as compared with 157 μmol L(-1) (Fe(II)) and 1219 μmol L(-1) (H2O2) for photo-Fenton reactions. Under these conditions, arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…Velásquez et al [46] reported that the degradation of STZ would begin with the attack of hydroxyl radical to benzene ring, with the formation of 4-hydroxy-N-(1,3-thiazol)-benzenesulfonamide (A4), releasing NH 4 + . Subsequently, the ring opening of this compound A4 takes place, which produces a complex mixture of carboxylic and dicarboxylic acids.…”
Section: àmentioning
confidence: 99%
“…Velásquez et al [46] reported that the degradation of STZ would begin with the attack of hydroxyl radical to benzene ring, with the formation of 4-hydroxy-N-(1,3-thiazol)-benzenesulfonamide (A4), releasing NH 4 + . Subsequently, the ring opening of this compound A4 takes place, which produces a complex mixture of carboxylic and dicarboxylic acids.…”
Section: àmentioning
confidence: 99%
“…Due to the drought-related stomata closure and overload of electron-transport chains, the rate of this process is essentially increased [151]. The formed O 2 − can be dismutated to hydrogen peroxide (H 2 O 2 ), which can further yield highly toxic hydroxide radical (OH · ), for example, by the Fenton reaction in the presence of certain transition metal ions [152]. On the PS II donor side, incomplete water oxidation also leads to H 2 O 2 production.…”
Section: Physiological and Biochemical Characterization Of Droughtmentioning
confidence: 99%
“…Various methods for the removal of antibiotics have been applied to purify water, such as conventional techniques (biological processes, filtration, coagulation/flocculation and sedimentation) [ 17 21 ], advanced oxidation processes (AOPs) [ 22 ], adsorption [ 23 ], membrane processes [ 24 ], ozonation [ 25 , 26 ], photochemical degradation [ 1 , 27 ], and Fenton/photo-Fenton processes [ 28 ]. Among the above water-treatment techniques described, adsorption is generally preferred for the removal of FQs due to its relevant characteristics of high efficiency, easy handling, availability of different adsorbents, and cost effectiveness [ 29 ].…”
Section: Introductionmentioning
confidence: 99%